Video documental cobertura televisiva sobre la campaña “matrimonio civil igualitario” realizada en el año 2013 - Medina Chicaiza, Micaela Clariza (2018)
The struggle for the GLBTI rights community in the world and in Ecuador has been present over time. Ecuador decriminalised homosexuality in 1997. Another important fact is given at the end of 2012 and early 2013, here the LGBTI movement sues presidential candidate Néstor Zavala, due to the fact that his speech was based on a direct aimed hatred against homosexuality, Pamela Troya together with her social rights collective won the trial against the candidate, this was known as the first LGBTI trial to have ever been won in the history of Ecuador. These are important reasons as to why sex-generic diversities fight for equal rights, as well as other background facts were important to the campaign "Matrimonio Civil Igualitario: los mismos derechos, con los mismos nombres” where Pamela Troya and Gabriela Correa, along with several GLBTI groups and activists seeked civil marriage for homosexual couples, this event caused an echo in mass media, therefore it’s rejection was visible among the ecuadorian society and the government in turn (Rafael Correa). This petition was denied in three stages and now lays in the Constitutional Court without any answer. Equal civil marriage is a clear example of the discriminatory spirit of the state and citizenship. This research is intended to capture in a documentary video the journalistic coverage of the campaign and exclusion of sex-generic diversities by the state and society, we intend that its viewers become aware of the phenomenon and adopt a critical position to open up new dialogue spaces.